Sodium Naphthalene-2,6-dicarboxylate: An Anode for Sodium Batteries - Cabañero, Joel M; Pimenta, Vanessa; Cannon, Kieran C; Morris, Russell E; Armstrong, A Robert (ChemSusChem, 2019)
The conjugated dicarboxylate sodium naphthalene-2,6-dicarboxylate (Na2 NDC) was prepared by a low-energy-consumption reflux method, and its performance as a negative electrode for sodium-ion batteries was evaluated in electrochemical cells. The structure of Na2 NDC was solved for the first time (monoclinic P21 /c) from powder XRD data and consists of π-stacked naphthalene units separated by sodium-oxygen layers. Through an appropriate choice of binder and conducting carbon additive, Na2 NDC exhibited a reversible two electron sodium insertion at approximately 0.4 V (vs. Na+ /Na) with remarkably stable capacities of approximately 200 mAh g-1 at a rate of C/2 and good rate capability (≈133 mAh g-1 at 5 C). In parallel, the high thermal stability of the material was demonstrated by high-temperature XRD: the framework remained intact to above 500 °C.
Keywords: organic redox; metal-organic frameworks (MOFs); Na ions; anodes; batteries